2011
DOI: 10.1002/hipo.20734
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area disruption selectively affects CA1/CA2 but not CA3 place fields during a differential reward working memory task

Abstract: Hippocampus (HPC) receives dopaminergic (DA) projections from the ventral tegmental area (VTA) and substantia nigra. These inputs appear to provide a modulatory signal that influences HPC dependent behaviors and place fields. We examined how efferent projections from VTA to HPC influence spatial working memory and place fields when the reward context changes. CA1 and CA3 process environmental context changes differently and VTA preferentially innervates CA1. Given these anatomical data and electrophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 42 publications
4
58
0
Order By: Relevance
“…3). Mankin et al 85 found that CA2 neurons, similar to those in the other CA fields, display place fields, consistent with a previous study that reported little difference in spatial firing between CA1 and CA2 neurons in rats exploring a radial arm maze 86 . However, CA2 place fields were later found to be slightly greater in number and larger in size than those in the CA1 and CA3 (REF.…”
Section: Role In Behavioursupporting
confidence: 73%
“…3). Mankin et al 85 found that CA2 neurons, similar to those in the other CA fields, display place fields, consistent with a previous study that reported little difference in spatial firing between CA1 and CA2 neurons in rats exploring a radial arm maze 86 . However, CA2 place fields were later found to be slightly greater in number and larger in size than those in the CA1 and CA3 (REF.…”
Section: Role In Behavioursupporting
confidence: 73%
“…VTA input to HPC may be direct (Gasbarri et al 1994), whereas HPC output to VTA is likely indirect, arriving via an accumbens to ventral pallidal to pedunculopontine nucleus route (Yang and Mogenson 1987;Floresco et al 2001). Supporting this view, VTA has been shown to regulate HPC neural activity during spatial learning (Martig and Mizumori 2011) and encoding of HPC-dependent memories (Rossato et al 2009). The pedunculopontine nucleus has been shown to regulate DA neuron firing (Kelland et al 1993;Floresco et al 2003;Zweifel et al 2009) and HPC regulates VTA DA neuron firing (Floresco et al 2001).…”
Section: Vta -Hpc Interactions During Learning and Memorymentioning
confidence: 99%
“…Intrahippocampal injections of DA agonists and antagonists improve and impair HPC-dependent behaviors, respectively (Packard and White 1991;Gasbarri et al 1996;Bernabeu et al 1997;O'Carroll et al 2006;Bethus et al 2010). The majority of DA innervations to HPC arise from the VTA (Gasbarri et al 1994), and VTA inactivation disrupts HPC-dependent learning, memory, and place fields Rossato et al 2009;Martig and Mizumori 2011). …”
mentioning
confidence: 99%
“…Martig et al, 2011a; Norton et al, 2011; Puryear et al, 2010). Each tetrode was made of four 25μm tungsten wires that were gold plated to achieve impedances of 100 to 400 kΩ.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…However, LDTg lesions result in the attenuation of drug-induced stereotypy and sensitization (Forster et al, 2002; Laviolette et al, 2000; Nelson et al, 2007), effects likely mediated via mesencephalic and medullary efferents that control patterned limb movements (Brudzynski et al, 1988; Mogenson et al, 1980). Here, we test the nature of LDTg neural codes in a task that a) has a strong and directed locomotion component, b) has a specific reward-based econometric demands, c) induces VTA and PPTg neural responses to reward value (Jo et al, 2013; Martig et al, 2011b; Norton et al, 2011; Puryear et al, 2010), and d) requires VTA functionality (Martig et al, 2009, 2011a). In Experiment 1, the LDTg was inactivated while rats performed a spatial-reward discrimination task.…”
Section: Introductionmentioning
confidence: 99%